Effect of Macroeconomic Factors on the Construction Sector Sharia Stock Price Index for the 2019-2021 Period - Selfi Pebriani; Dedi Suselo (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2022)
This study aims to examine the effect of macroeconomics, namely the effect of Exchange Rate, Inflation, BI-7 Day Repo Rate, and Gold Price on the Construction Sector Stock Price Index listed on the Jakarta Islamic Index for the 2019-2021 period during the Covid-19 pandemic. The population used in this study are all those who are included in the building construction sector. The sample in this study is one of the construction companies listed in the Jakarta Islamic Index. The method of analysis in this study uses multiple linear regression analysis. The data collection technique in this research is purposive sampling. Purposive sampling is a technique in determining the research sample by using various considerations or based on the objectives of the researcher. The results of this study indicate that partially and simultaneously Exchange Rate Variable, Inflation, Interest Rate BI-7 Day Repo Rate, and Gold Price have a significant effect on the Construction Sector Stock Price Index. Variables Exchange Rate, Inflation, BI-7 Day Repo Rate, and Gold Price have a significant influence on the dependent variable, namely the Stock Price Index. It can be proven that all independent variables jointly have a significant effect, it can be proven.